THE EXISTENCE OF WOMEN CAMERAMEN IN PRODUCTION OF TELEVISION EVENTS IN INDOSIAR - Rusman Latief; Yusiatie Yusiatie (Jurnal Ilmiah Publipreneur, 2022)
Women cameramen is a new profession in Indosiar in early 2014. Previously, the profession of cameramen was only for men. Due to the need for that position, recruitment was carried out in which women were allowed. This research is interesting because it turns out that getting a woman who wants to be cameramen is not an easy matter. Therefore, it aims to seek and find answers to the existence of female cameramen in Indosiar. About how the recruitment, how the technical mastery skills of various types of cameras. Skills in using a camera concerning cinematography. What are her responsibilities in the production of broadcast programs, as well as the company's rules for women cameramen. This research uses a qualitative case study method. Using multiple sources to get valid data. Literature study, observation, and interviews, with several respondents who are considered to represent this research. Both respondents are still working at Indosiar, as well as those who have retired or have moved to other television stations. From the results of this research, it is hoped that it can contribute to the development of the television industry in Indonesia, the development of audio-visual production in general, and can also provide information on the field of work for women to have a career in camera management in the television, film and other audio-visual industries.